menu
QAmmunity.org
Login
Register
My account
Edit my Profile
Private messages
My favorites
Register
Ask a Question
Questions
Unanswered
Tags
Categories
Ask a Question
Prove cos (x - n) = -cOS X. cos (x - 7) = cos x sin n - sin x cos n = -cos X cos (x - n) = cos x cos n - sin x sin n = -cos X cos (x - n = cos x sinn + sin x cos n = -cos X cos (x - n) = cos x cos n +
asked
Jun 22, 2021
184k
views
1
vote
Prove cos (x - n) = -cOS X.
cos (x - 7) = cos x sin n - sin x cos n = -cos X
cos (x - n) = cos x cos n - sin x sin n = -cos X
cos (x - n = cos x sinn + sin x cos n = -cos X
cos (x - n) = cos x cos n + sin x sin n = -cos x
Mathematics
middle-school
Lucamuh
asked
by
Lucamuh
5.0k
points
answer
comment
share this
share
0 Comments
Please
log in
or
register
to add a comment.
Please
log in
or
register
to answer this question.
1
Answer
2
votes
Answer:
Answer B
Explanation:
cos n + x =cos x + y
Huggie
answered
Jun 26, 2021
by
Huggie
4.8k
points
ask related question
comment
share this
0 Comments
Please
log in
or
register
to add a comment.
Ask a Question
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.
5.3m
questions
6.8m
answers
Other Questions
Pizza planet is running a special 3 pizzas for 16.50. What is the unit rate for one pizza
What number is halfway between 0 and 18
If the 9-inch wheel of cheese costs $18.60, what is the cost per square inch? If the cost is less than a dollar, put a zero to the left of the decimal point?
how long Will it take for $7000 investment to grow to $7553 and the annual rate of 3.4% compounded quarterly assume that no withdrawals are made
I need to simplify this expression.
Twitter
WhatsApp
Facebook
Reddit
LinkedIn
Email
Link Copied!
Copy
Search QAmmunity.org